The role of HTA agencies in Poland and in the world - Aneta Katarzyna Mela (Polish Pharmaceutical Society, 2020)
Health Technology Assessment (HTA) is a foundation of submitting applications for reimbursement of a particular health technology. It involves conducting comparative analyzes in which the existing health care standard is compared with the new technology in order to test the benefits of introducing financing of the new technology. There are several dozen authorities responsible for HTA in various countries around the world. The structures, functions, competences and approaches of individual HTA agencies differ due to differences in healthcare systems, as well as due to the heterogeneous political structures in which they operate. In some countries, HTA agencies are responsible only for the HTA assessment process, consisting of reviewing scientific evidence and data synthesis, while in others also for verifying and making a reimbursement decision, based on, among others budget restrictions. However, regardless of the structures and competences of the HTA agencies in individual countries, the introduction of HTA as a tool for rational reimbursement decisions in various healthcare systems has significantly reduced the uncertainty associated with their making. Poland is an example of a country where no medicine is reimbursed without formal procedures. It is not possible for a drug to be reimbursed in a new medical indication, without an assessment of health technologies. Following the example of other developed countries, Poland in 2005 introduced a health technology assessment system to the drug reimbursement process by establishing an advisory body for the Minister of Health - the Agency for Health Technology Assessment, which tasks include in particular, developing recommendations regarding the financing of health technologies. In accordance with the guidelines of the president of AOTMiT, the drug manufacturer, in addition to analyzing the decision problem, have to prepare three types of analysis: the clinical effectiveness analysis, the economic analysis and the analysis of the impact on the healthcare system.